2008
DOI: 10.1186/1477-7827-6-59
|View full text |Cite
|
Sign up to set email alerts
|

Serial analysis of gene expression reveals differential expression between endometriosis and normal endometrium. Possible roles for AXL and SHC1 in the pathogenesis of endometriosis

Abstract: Background: Endometriosis is a clinical condition that affects up to 10% of the women of reproductive age. Endometriosis is characterized by the presence of endometrial tissues outside the uterine cavity and can lead to chronic pelvic pain, infertility and, in some cases, to ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 47 publications
2
54
0
1
Order By: Relevance
“…It has been reported that NUCB2 protein and its binding sites are expressed in mouse uterus, and play pivotal roles in the collapse and recovery of endometrium [26]. Honda et al also found out that NUCB2 expression was differentially detected in endometriosis by Serial Analysis of Gene Expression (SAGE) methods [27]. These findings all suggest the importance of NUCB2 in endometrial disorders as well as normal endometrium.…”
Section: Discussionmentioning
confidence: 58%
“…It has been reported that NUCB2 protein and its binding sites are expressed in mouse uterus, and play pivotal roles in the collapse and recovery of endometrium [26]. Honda et al also found out that NUCB2 expression was differentially detected in endometriosis by Serial Analysis of Gene Expression (SAGE) methods [27]. These findings all suggest the importance of NUCB2 in endometrial disorders as well as normal endometrium.…”
Section: Discussionmentioning
confidence: 58%
“…Studies on the differences in gene expression between the ectopic and eutopic endometrium (17)(18)(19)(20)(21)(22) have found that many genes related to cell adhesion, cell migration, cell proliferation, immune regulation and inflammation are differentially expressed in ectopic vs. eutopic endometrial tissue. In the study by Ohlsson Teague et al (12), it was suggested that c-Jun mRNA expression was significantly increased in endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown before that the PI3K/Akt signaling pathway is abnormally activated during endometriosis and that this activation was partly responsible for the endometriotic cells' reduced decidual response (Matsuzaki et al 2005, Cinar et al 2009); serial analysis of gene expression revealed an increased level of both PI3K and phosphorylated AKT (S473) in endometriotic tissues, probably through the enhanced expression of GAS6, AXL, and ACTN4, responsible for enhanced proliferation and motility (Honda et al 2008). On the other hand, AKT was not involved in endometriotic cells' expression of EMT markers in response to TNFa, a crucial component of inflammation in this disease (Berkkanoglu & Arici 2003, Grund et al 2008.…”
Section: Endometriosismentioning
confidence: 99%
“…Increased and decreased expression of phosphorylated AKT (S473) is usually concomitant with similar changes in the activity of mTORc1, leading us to think that one of the primary effect of AKT in endometriosis is the activation of the mTOR pathway (Lucidi et al 2005, Honda et al 2008, Zhang et al 2009). The NFkB pathway also seems to be entwined in the hormonal response as well as survival mechanisms in which AKT is involved (Grund et al 2008, Zhang et al 2010, Capp et al 2011.…”
Section: Endometriosismentioning
confidence: 99%